Do amnesty programs encourage illegal immigration? Evidence from the Immigration Reform and Control Act (IRCA) - Pia M. Orrenius; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2001)
This paper examines whether allowing certain undocumented immigrants to legalize their status leads to additional illegal immigration. The authors focus on the effects of the 1986 Immigration Reform and Control Act, which granted amnesty to over three million undocumented immigrants. They find that apprehensions of persons attempting to illegally cross the U.S.-Mexico border declined immediately following passage of the law but returned to normal levels during the period when illegal immigrants could file for amnesty and in the years thereafter. The authors' findings suggest that the amnesty program did not change long-term patterns of illegal immigration from Mexico.
Keywords: 330; Immigration Reform and Control Act of 1986